Management of Fibro-adipose Vascular Anomalies (FAVA) in Paediatric Practice. (September 2021) - Lipede, C; Nikkhah, D; Ashton, R; Murphy, G; Barnacle, AM; Patel, PA; Smith, GD; Eastwood, DM; Sivakumar, B
Abstract: Fibro-adipose vascular anomaly (FAVA) is a discrete type of vascular anomaly. We describe our experience managing FAVA at a tertiary level paediatric hospital and offer a treatment algorithm. Methods: A retrospective review of 27 patients with proven FAVA was undertaken. All patients had undergone MRI and USS evaluation. Patient demographics, presenting concerns, treatment methods, and outcomes were recorded and evaluation with the paediatric outcomes data collection instrument (PODCI) completed a minimum of 12 months after definitive treatment. Results: Mean age at presentation was 8.9 years (range: 9 m-17.4 y) and mean post-treatment follow-up was 7.4 y (range: 2 y-11.6 y). Twenty of 27 lesions affected the lower limb. Severe neurogenic-type pain was present in 23 cases and contractures across joints in 11 cases. Sclerotherapy with sodium tetradecyl sulphate was used in 11 cases, with no improvement in symptoms. Cryoablation provided pain relief in 3/4 cases, but contracture subsequently increased in one patient and pain recurred in another. Fourteen cases underwent surgery (four surgical excisions alone, 10 in combination with other procedures). Three patients required four further surgical procedures that include one amputation for intractable pain and poor function. PODCI evaluations suggest overall good function, with surgical management and interventional radiology that provide comparable results. Surgery did correct deformity. Conclusion: If conservative measures or cryoablation fail to achieve symptomatic control, surgical excision should be considered, combined with adjunctive procedures, to correct contractures and balance muscle forces. Relief of pain may compensate for the loss of muscle mass and overall improves function. Multidisciplinary team working is essential.